2016
DOI: 10.1016/j.tim.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Viral Carcinogenesis Beyond Malignant Transformation: EBV in the Progression of Human Cancers

Abstract: Cancer progression begins when malignant cells colonize adjacent sites, and it is characterized by increasing tumor heterogeneity, invasion and dissemination of cancer cells. Clinically, progression is the most relevant stage in the natural history of cancers. A given virus is usually regarded as oncogenic because of its ability to induce malignant transformation of cells. Nonetheless, oncogenic viruses may also be important for the progression of infection-associated cancers. Recently this hypothesis has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 92 publications
(115 reference statements)
1
91
0
3
Order By: Relevance
“…12 Epstein-Barr virus (EBV) plays a crucial role in carcinogenesis, diagnosis and prognosis of nasopharyngeal cancer, also having clinical use in posttreatment surveillance. 29 There are small-series studies from…”
Section: Nasopharyngeal Cancermentioning
confidence: 99%
“…12 Epstein-Barr virus (EBV) plays a crucial role in carcinogenesis, diagnosis and prognosis of nasopharyngeal cancer, also having clinical use in posttreatment surveillance. 29 There are small-series studies from…”
Section: Nasopharyngeal Cancermentioning
confidence: 99%
“…It is a causative agent for IM (commonly known as kissing disease) and has also been detected in oral hairy leukoplakia [16]. Previous reports have shown that particular latent EBV-transcription programs are exhibited in numerous human tumors, including immunoblastic lymphoma in immunosuppressed patients, Burkitt lymphoma, Hodgkin's lymphoma, and nasopharyngeal carcinoma (NPC) [2,4,17,18]. These typical expression patterns act as rough guidelines to aid in the clinicopathological diagnosis of every type of EBV [4,17].…”
Section: Ebv-associated Diseasesmentioning
confidence: 99%
“…Previous reports have shown that particular latent EBV-transcription programs are exhibited in numerous human tumors, including immunoblastic lymphoma in immunosuppressed patients, Burkitt lymphoma, Hodgkin's lymphoma, and nasopharyngeal carcinoma (NPC) [2,4,17,18]. These typical expression patterns act as rough guidelines to aid in the clinicopathological diagnosis of every type of EBV [4,17]. The investigation of patients with EBV-infected tumors has provided a reasonable degree of proof that EBV was present before neoplastic transformation, which highlights the need to further elucidate how much EBV contributes to tumorigenesis [4].…”
Section: Ebv-associated Diseasesmentioning
confidence: 99%
“…1 Several molecules encoded by EBV in its latent phase are thought to be associated with carcinogenesis in various cancers including nasopharyngeal cancer, gastric cancer, classic Hodgkin lymphoma, and some types of non-Hodgkin lymphoma. [2][3][4] Among them, extranodal natural killer/T-cell lymphoma, nasal type (ENKL) is highly associated with EBV infection in terms of its pathogenesis. 5 EBV-encoded RNA1 (EBER1) is a non-coding small RNA with 167 nucleotides.…”
Section: Introductionmentioning
confidence: 99%